PET imaging to assess fibroblast activation protein inhibitor biodistribution: A training program adapted to pharmacology education. Issue 4 (11th August 2022) - Ge, Luna; Song, Guanhua; Zhang, Yuang; Pan, Jihong; Zhang, Yihang; Wang, Lin; Cheng, Kai
Abstract: In the process of pharmacology education, practical teaching is an important complement to theoretical teaching. These activities include the use of experimental animals to obtain certain pharmacological parameters or to help students understand certain classical concepts. However, the growing interest in laboratory animal welfare, the rapid development of pharmacology research and the challenges of cultivating innovative pharmacy talent create a need for innovative and flexible in vitro experiments for teaching purposes. Here, we report the application of positron emission tomography (PET) imaging of 18 F‐labeled fibroblast activation protein inhibitor ( 18 F‐FAPi) to practical pharmacology teaching, enabling dynamic visualization of the distribution and excretion process of FAPi in mice. Students can quantitatively analyze the distribution of FAPi in various tissues and organs without sacrificing the mice. Furthermore, the newly implemented method resulted in highly reproducible results and was generally appreciated by the students. Additionally, the application of PET imaging in pharmacokinetic teaching can not only greatly reduce the use of experimental animals but also need not sacrificing animals. Of note is that dynamic scanning data from this project can be used for online practical teaching during COVID‐19 pandemic. Abstract : PET imaging, a non‐invasive method for determination of pharmacokinetics in live animals, will not only visualize the distribution and excretion process of drugs in pharmacology teaching, but will also greatly reduce the use of laboratory animals.